At the x-intercept the value of the y-coordinate is 0. So to find the x-intercept of y = x^2 – 4x + 4 we can substitute y = 0 and solve.

x^2 – 4x + 4 = 0

=> (x - 2)^2 = 0

we get x = 2.

**Therefore the x-intercept is (2 , 0)**

Given the equation of the curve y= x^2 - 4x + 4

We need to find the x-intercept .

We know that the c-intercept is the point where the curve y meets the x-axis.

When the curve touches the x-axis, the values of y will be 0.

==> y= x^2 - 4x + 4 = 0

Now we will factor.

==> (x-2)(x-2) = 0

==> x = 2

**Then, the x-intercept is the point ( 2, 0).**